Teknik Relaksasi Napas Dalam Dapat Meningkatkan Status Hemodinamik Pasien Hipertensi - Hayati, Teti; Harini, Rika; Amikarois, Amikarois; Jelatu, Veronika Ace; Makualaina, Fenska Narli (Journal of Telenursing (JOTING), 2023)
This study aims to determine whether deep breathing relaxation techniques can improve the hemodynamic status of hypertensive patients. This research method uses a cross-sectional design. The results of this study show that the p-value = 0.000 is smaller than the α = 0.05, which means that there is an influence of deep breathing relaxation techniques in improving the hemodynamic status of hypertensive patients. Conclusion The patient's deep breathing relaxation technique increases the patient's oxygen saturation before and after deep breathing relaxation. Keywords: Hemodynamics, Hypertension, Patients, Breath Relaxation Techniques